1995
DOI: 10.1172/jci118238
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glutathione S-transferase B (ligandin) on the intermembrane transfer of bilirubin. Implications for the intracellular transport of nonsubstrate ligands in hepatocytes.

Abstract: IntroductionTo examine the hypothesis that glutathione S-transferases (GST) play an important role in the hepatocellular transport of hydrophobic organic anions, the kinetics of the spontaneous transfer of unconjugated bilirubin between membrane vesicles and rat liver glutathione S-transferase B (ligandin) was studied, using stopped-flow fluorometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

1996
1996
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 63 publications
(62 reference statements)
0
13
1
Order By: Relevance
“…They are good examples of combined effects of mutations of UGT1A1 and other genes. Recently, two other proteins related to neonatal jaundice have been investigated with regard to overflow of nonconjugated bilirubin from the liver; transporter proteins of bilirubin in hepatic cells encoded by the organic anion transporter 2 gene (OATP2 or SLC21A6) (31,32) and the glutathione-Stransferase gene (GST) (33,34). However, combined effects of c.-3279TϾG in UGT1A1 and hemolytic disorder-causing genes and combined effects of c.-3279TϾG and OATP2 (or GST) mutations remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…They are good examples of combined effects of mutations of UGT1A1 and other genes. Recently, two other proteins related to neonatal jaundice have been investigated with regard to overflow of nonconjugated bilirubin from the liver; transporter proteins of bilirubin in hepatic cells encoded by the organic anion transporter 2 gene (OATP2 or SLC21A6) (31,32) and the glutathione-Stransferase gene (GST) (33,34). However, combined effects of c.-3279TϾG in UGT1A1 and hemolytic disorder-causing genes and combined effects of c.-3279TϾG and OATP2 (or GST) mutations remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins of class A GSTs bind to bilirubin with a higher affinity than those of the M and T classes [10,24,28,31,38]. Contrary to this generally held concept regarding the role of GSTs in the intracellular transport of nonsubstrate ligands, Boyer and Whalen suggested that all of the GSTs appear to bind to nonsubstrate ligands such as bilirubin [2,37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to detoxification, certain GSTs such as the alpha class GST isoforms in humans (hGSTA1-1) (Zucker et al, 1995) and rats (rGSTA1-1, rGSTA3-3) (Sheehan and Mantle, 1984), as well as human pi-class GST (hGSTP1-1) (Caccuri et al, 1990;Kaplowitz, 1980;Oakley et al, 1999) exhibit ligandin properties by binding and sequestering endogenous and exogenous compounds (Hayes and Pulford, 1995;Singer and Litwack, 1971;Tipping and Ketterer, 1981;Tipping et al, 1976). Ligandin substrates can include toxicants such as reactive metabolites formed from carcinogens (Arias et al, 1980;Kirsch et al, 1975) as well as endogenous compounds such as heme and bilirubin (da Silva Vaz et al, 2004;Di Ilio et al, 1995;Litwack et al, 1971).…”
Section: Discussionmentioning
confidence: 99%